The lymphatic vasculature in lung function and respiratory disease - Trivedi, Anjali; Reed, Hasina Outtz (Frontiers in Medicine, 2023)
The lymphatic vasculature maintains tissue homeostasis via fluid drainage in the form of lymph and immune surveillance due to migration of leukocytes through the lymphatics to the draining lymph nodes. Lymphatic endothelial cells (LECs) form the lymphatic vessels and lymph node sinuses and are key players in shaping immune responses and tolerance. In the healthy lung, the vast majority of lymphatic vessels are found along the bronchovascular structures, in the interlobular septa, and in the subpleural space. Previous studies in both mice and humans have shown that the lymphatics are necessary for lung function from the neonatal period through adulthood. Furthermore, changes in the lymphatic vasculature are observed in nearly all respiratory diseases in which they have been analyzed. Recent work has pointed to a causative role for lymphatic dysfunction in the initiation and progression of lung disease, indicating that these vessels may be active players in pathologic processes in the lung. However, the mechanisms by which defects in lung lymphatic function are pathogenic are understudied, leaving many unanswered questions. A more comprehensive understanding of the mechanistic role of morphological, functional, and molecular changes in the lung lymphatic endothelium in respiratory diseases is a promising area of research that is likely to lead to novel therapeutic targets. In this review, we will discuss our current knowledge of the structure and function of the lung lymphatics and the role of these vessels in lung homeostasis and respiratory disease.